The Analysis of Predisposing and Reinforcing Factors on the Accuracy of Returning Inpatient Medical Records Documents - Atma Deharja; Fatika Laily Novitasari; Ervina Rachmawati; Maya Weka Santi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
According to the Procedure Operational Standard of Jember Klinik Hospital, the time for returning medical record documents is 2x24 hours after the patient's discharged from the hospital. Therefore, a medical record document return system is essential to support services, especially medical record document management. Based on the preliminary study, the average rate of returning medical record documents more than 48 hours from January to June 2019 reached 42.3%. The purpose of this study was to analyze the relationship between predisposing and reinforcing factors on the accuracy of returning inpatient medical record documents at the Jember Klinik Hospital. It is a quantitative study with a cross-sectional approach and the spearman rank correlation method. The population of this study was 67 nurses and midwives and 50 respondents as the sample. The results were that there was a significant relationship between knowledge (sig. 0,000), attitude (sig. 0.009), superiors support (sig. 0.002), and colleagues support (sig. 0.012) on the accuracy of returning medical record documents. However, the variable age (sig. 0.110) of nurses and midwives has no significant relationship with the precision of returning medical record documents. Therefore, this study can be used as a reference in evaluating the accuracy of returning medical record documents. Abstrak: Waktu pengembalian dokumen rekam medis menurut Standar Operasional Prosedur Rumah Sakit Jember Klinik maksimal 2x24 jam setelah pasien keluar dari rumah sakit. Sistem pengembaliandokumenrekammedissangatpentinguntuk menunjangpelayanankhususnya  dalam pengolahan  dokumen  rekam medis. Berdasarkan hasil studi pendahuluan di Rumah SakitJember Klinik diketahui bahwa angka rata-rata pengembalian dokumen rekam medis ke unit kerja rekam medis lebih dari 48 jam (2x24jam) pada bulan Januari hingga Juni 2019 mencapai 42,3%. Tujuan dari penelitian ini adalah menganalisis hubungan faktor predisposisi dan penguat terhadap ketepatan pengembalian dokumen rekam medis rawat inap di Rumah Sakit Jember Klinik. Jenis penelitian ini merupakan penelitian kuantitatif dengan pendekatan crosssectional dan metode korelasi spearman rank. Populasi penelitian ini yaitu sebanyak 67 petugas rawat inap dan sampel 50. Hasil penelitian yang dilakukan oleh peneliti yaitu bahwa terdapat hubungan yang signifikan antara pengetahuan (sig. 0,000), sikap (sig. 0,009), dukungan atasan (sig. 0,002), dan dukungan rekan kerja (sig. 0,012) terhadap ketepatan pengembalian dokumen rekam medis. Namun variabel usia (sig. 0,110) perawat atau bidan tidak ada hubungan yang signifikan dengan ketepatan pengembalian dokumen rekam medis. Hasil penelitian ini dapat digunakan sebagai bahan  evaluasi  bagi  pihak  rumah  sakit dalam evaluasi ketepatan pengembalian dokumen rekam medis.